KINERJA YAYASAN MAHA BHOGA MARGA BERBASIS BALANCED SCORECARD: Studi pada Yayasan Maha Bhoga Marga - I Made Dwi Semara Putra; Ni Luh Putu Wiagustini (Universitas Triatma Mulya, 2021)
Measurement performance of organization is the one of the most important thing for going concern of organization. In Non Government Organization to realize the vision and mission to achieve the organization’s goal is an achievement that can measure the success of the organization in evaluating the results of activities carried out by the organization compared to a predetermined benchmark. Balanced Scorecard is a measurement tool as a counterweight to the financial aspect and the non-financial aspects, such as customer / assisted satisfaction, internal business processes, learning and growth within the company. This study aims to analyze how Maha Bhoga Marga Foundation can meet, customer needs, business process interactions that need to be developed internally and how also with aspects of employee development in the learning process and growth and financial needs as a strategy to improve its performance. This research was conducted at Maha Bhoga Marga Foundation in Bali. The method used in this research is descriptive method by analyzing data from four perspectives: the customer perspective with customer satisfaction index and learning and growth with employee satisfaction index, internal business process perspective, financial perspective as measured by average comparation of revenue and expenses value. The results of the analysis show that the performance of Maha Bhoga Marga Foundation is categorized as Good. It is assessed from Balance Scorecard analysis which shows: 1) Service User's Perspective is in very good category, 2) Process Perspective The Internal, and 3) the Learning and Growth Perspective is in a good category, 4) Based on the average comparation of revenue and expenses vaalue achieved by Maha Bhoga marga Foundation, which decreased from the year during the period 2015-2017 shows the condition of Maha Bhoga Marga which have increased program are not following with increased income. This means the performance of the Financial Perspective of Maha Bhoga Marga Foundation sustainability is not good.